(untitled) (Research, Society and Development, 2022)
Consumers are increasingly looking for foods that have compounds that are beneficial to health, also called bioactive or photochemical, which are substances derived from the secondary metabolism of vegetables. Brazil has one of the greatest biodiversity in the world, with unexplored sources of native fruits with high levels of bioactive compounds. Among these fruits, the araçá (Psidium cattleianum Sabine) stands out. Araçá, in addition to its high nutritional value, has significant amounts of phenolic compounds, with epicatechin and gallic acid as its main components, unsaturated fatty acids and carotenoids. For presenting these characteristics, it is being considered a promising plant for the pharmaceutical and food industry due to its potential application as a herbal and functional food, among others. In this sense, this work aims to present a literature review on araçá and its benefits.